Histone Deacetylase Inhibitor Trichostatin A Reduces Endothelial Cell Proliferation by Suppressing STAT5A-Related Gene Transcription - Li, Yize; Zhao, Yongmei; Peng, Hongyan; Zhang, Jing; Bo, Lun; Wen, Lei; Liu, Wenchao; Bai, Wendong; Zhang, Hongmei (Frontiers in Oncology, 2021)
Inhibitors of histone deacetylases (HDACi) have shown promising effects in preclinical applications for the treatment of many diseases. Confusedly though, the effects of the HDACi trichostatin A (TSA) on angiogenesis are variable among different diseases. This study investigated the direct effects of TSA on endothelial cells, which play essential roles in angiogenesis, and the underlying molecular events. TSA reduced the viability of human umbilical vein endothelial cells (HUVECs), and in which proliferation-related genes including BIRC5, CKS1B, NDC80 were found to be involved. Further, signal transducer and activator of transcription 5 A (STAT5A) was demonstrated to be reduced by TSA and to mediate TSA-induced downregulation of BIRC5, CKS1B and NDC80 and HUVECs proliferation. Mechanistically, data showed that STAT5A directly bound to the promoters of BIRC5, CKS1B, NDC80 and activated their transcription through special DNA sequence sites. Finally, TSA-STAT5A-BIRC5, CKS1B and NDC80 axis were also worked in a cancerous endothelial cell angiogenesis model. The results of this study revealed novel mechanisms underlying the effects of TSA on endothelial cells and provided insights for angiogenesis associated diseases.